Relationship between learner variables and Malaysian students' willingness to communicate in the ESL classroom - Chandra Segar, Koggila (2018)
The four language skills of listening, speaking, reading and writing are all interconnected. Proficiency in each skill is needed to become an efficient communicator. Furthermore, the ability to communicate fluently provides speaker with various benefits. This dissertation evaluates the willingness to communicate (WTC) in English Language among Malaysian students. WTC is the most basic orientation towards communication. Almost anyone is likely to respond to a direct question, but many will not continue or initiate interaction. This study is conducted in the light of a previously laid down theory, WTC of McCroskey & Richmond (1987). The research is tested in five different dimensions, namely, opportunity to communicate with foreigner, teachers, language competency, gender and age groups. The study is conducted in Linton University College, Mantin, Negeri Sembilan, Malaysia. A total of 15 degree and 88 non degree Malaysian students are selected using a simple random sampling technique. McCroskey’s (1992) & MacIntyre’s (1998) questionnaires are referred to in designing the questionnaire for the purpose of this study, which are then analysed using the Statistical Package for Social Sciences (SPSS) version 21.0. Whereas, a structured face-to-face interview is conducted to acquire a better comprehension on the study. Accordingly, a thematic analysis is used to analyse the qualitative data. Thus, the current study adopts a mixed method with an explanatory design. The opportunity to communicate with foreign learners shows a positive outcome on this study. However, teachers and language competency tend to decrease Malaysian students’ WTC. Although, female students’ level of WTC is higher than the male students, there is no significant difference. The outcome of this research, aims at encouraging educators to come up with effective teaching approaches to increase learners’ WTC in English language and to attract more international students to enrol in Malaysian universities. To date, the WTC construct has not been widely tested in a Malaysian context. Hence, the current study is a significant addition to the context of Malaysian students’ WTC.